Reading Auschwitz - Lagerwey, Mary Deane (Ethnographic alternatives series, 1998)
Borrowed memories and grand narratives -- Different horrors -- Situated voices -- Chaos -- Reflections -- Appendix : book-length published memoirs of Auschwitz available in English